DEVELOPMENT OF MATHEMATICS LEARNING DEVICES WITH PROBLEM BASED LEARNING ON SOCIAL ARITHMETIC MATERIALS FOR STUDENTS OF CLASS VII SMP/MTs - Ronny Saputra; Sehatta Saragih (Jurnal Prinsip Pendidikan Matematika, 2022)
This research produces mathematics learning tools in the form of syllabus, lesson plans (RPP), and student worksheets (LKPD) based on the Problem Based Learning model of social arithmetic material for seventh-grade junior high school students. This study uses a 4-D development model which includes four stages, namely: (1) define (define); (2) design (planning); (3) develop (development); and (4) spread (spread). The research instrument used is the instrument of validity and practicality. The validity instrument is in the form of a validation sheet to assess the feasibility of the syllabus, lesson plans, and LKPD. The practicum instrument is in the form of a student response questionnaire to use LKPD. The learning tools that have been compiled are then validated by three validators and revised according to suggestions from the validators. The valid learning tools were then tested in the readability test with four seventh grade junior high school students and a small group trial with nine junior high school class VII students as the subject. Based on the data analysis and discussion results, mathematics learning tools in the form of syllabus, lesson plans, and LKPD based on Problem-Based Learning models on social arithmetic material are considered very valid and practical to be used by class VII junior high school students.